Asymptotic periodicity of trajectories of an interval - Fedorenko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We consider dynamical systems generated by continuous mappings of an interval I into itself. We prove that the trajectory of an interval J ⊂ I is asymptotically periodic if and only if J contains an asymptotically periodic point.